Cost-effectiveness of high dose versus adjuvanted trivalent influenza vaccines in England and Wales. (1st January 2021) - Mattock, Richard; Gibbons, Ilana; Moss, Joe; Mealing, Stuart; Largeron, Nathalie; Carroll, Stuart; Alvarez, Fabián P.
Abstract: Aims: High dose trivalent influenza vaccine (HD TIV) and adjuvant TIV (aTIV) have been developed specifically for adults aged 65 and older (65+) who are at high risk of life-threatening complications. However, there is a scarcity of evidence comparing the clinical and cost-effectiveness of HD TIV and aTIV. The aim of this study was to determine the cost-effectiveness of HD TIV versus aTIV in the England and Wales 65+ population. Methods: A cost-utility analysis was conducted using a decision tree with two influenza related outcomes: Laboratory confirmed cases that could result in GP consultation, and hospitalizations that may result in premature mortality. Due to a lack of comparative evidence, the effectiveness of HD TIV versus aTIV was calculated indirectly, based on relative effectiveness estimates for each vaccine versus a common comparator, standard dose (SD) TIV. The primary analysis included hospitalizations explicitly due to influenza/pneumonia. Cost-effectiveness was established for three scenarios applying differing relative effectiveness estimates for aTIV versus SD TIV. Uncertainty was analysed in one-way deterministic sensitivity analyses. A secondary analysis included hospitalizations due to any respiratory illness. Results: The minimum population impact of vaccination with HD TIV rather than aTIV was 13, 092 fewer influenza cases, 1, 109 fewer influenza related deaths, 4, 673 fewer hospitalizations, and 3, 245 fewer GP appointments. HD TIV was cost-effective versus aTIV for all three effectiveness scenarios, with incremental cost-effectiveness ratios (ICER) equal to £1, 932, £4, 181, and £8, 767 per quality adjusted life year. Results were consistent across the secondary analysis and deterministic sensitivity analyses. Limitations: The analysis was limited by a lack of robust and consistent effectiveness data for aTIV. Conclusion: HD TIV is cost-effective versus aTIV in people aged 65+ in England and Wales. Use of HD TIV over aTIV could increase clinical benefits and reduce the public health and economic burden of influenza.